A hipótese da lavratura do termo circunstanciado de ocorrência pelas polícias militares estaduais, polícia federal e polícia rodoviária federal - Silva, Marcos Paraíso da (2020)
The present work has as general objective to approach discussion about a specific procedure of the Criminal Law, and its relevance to the Public Security fundamental right, seeking precisely the effectiveness of democracy. The paper presents the possibility of drawing up the Circumstance of Occurrence of Occurrence by the different police institutions, according to Law No. 9,099 / 95, by assigning the Circunstanced Term of Occurence to the police authority, without specific explanations. This law defines the procedures with the Special Civil and Criminal Courts and other deliberations, therefore, this set of rules takes over the ability of conciliation by the State Military Police and Federal Highway Police in relation to the minor potential offenses. The Circumstance of Occurrence completed by non-investigative police could bring positive results in relation to the services rendered to the community, as it amplifies the police force to the public service, an idea that meets the defense of democracy and public security. It is concluded from this study that the major key point in the procedures adopted by police should be the safety and quality of public service, so that the Circunstanced Term of Occurence of criminal offenses situations could be worked out by military state police and federal road police, in addition to investigative police forces thus offering the community a fast and effective public security service.